Screening Action Potentials: The Power of Light - Kaestner, Lars; Lipp, Peter (Frontiers in Pharmacology, 2011)
Action potentials reflect the concerted activity of all electrogenic constituents in the plasma membrane during the excitation of a cell. Therefore, the action potential is an integrated readout and a promising parameter to detect electrophysiological failures or modifications thereof in diagnosis as well as in drug screens. Cellular action potentials can be recorded by optical approaches. To fulfill the pre-requirements to scale up for e.g. pharmacological screens the following preparatory work has to be provided: (i) model cells under investigation need to represent target cells in the best possible manner; (ii) optical sensors that can be either small molecule dyes or genetically encoded potential probes need to provide a reliable readout with minimal interaction with the naive behavior of the cells and (iii) devices need to be capable to stimulate the cells, read out the signals with the appropriate speed as well as provide the capacity for a sufficient throughput. Here we discuss several scenarios for all three categories in the field of cardiac physiology and pharmacology and provide a perspective to use the power of light in screening cardiac action potentials.